The role of civil society in conflict transformation in Zimbabwe: the case of Heal Zimbabwe Trust - Mangwiro, Innocent (Midlands State University, 2017)
This study seeks to analyse the role of civil society in Conflict Transformation in Zimbabwe using the case study of Heal Zimbabwe Trust. The study takes a look into the nature of conflicts in Zimbabwe that date back to the period of the liberation struggle, the Gukurahundi massacres, land invasions, operation Murambatsvina and the 2008 political violence. A critique is given to the work of the civil society organisations on conflict resolution, management, settlement and mitigation. The study goes on to look into conflict transformation initiatives by Heal Zimbabwe that seek to promote peaceful relations out of animosity, including collaborative platforms, women safe spaces for reconciliation and sports for peace tournaments.. The successes and challenges that Heal Zimbabwe face in transforming conflicts are given, with reduced violence in the 2013 elections, tolerance and social cohesion in some communities as successes. The challenges include the denial of operating space by the state through bureaucratic means to acquire a memorandum of understanding, the organisation’s financial challenges and its inability to find sustainable ways to peace building. A conclusion was drawn and some recommendations were made out by the researcher basing on the research findings of the study.